The Use of Syllable Card Media to Enhance Elementary School Students' Reading Readiness - Yuli Sulistyowati Puji Rahayu; Banun Havifah Cahyo Khosiyono; Ana Fitrotun Nisa; Berliana Henu Cahyani (Jurnal Ilmiah Sekolah Dasar, 2025)
Reading skills are fundamental competencies for elementary school students, yet early grade students often face difficulties due to the lack of engaging learning media appropriate to their developmental characteristics. Learning activities will be more meaningful if supported by media that can motivate students, especially those aged 7–8 years, who are still dominated by a strong sense of play. This study aims to analyze the effectiveness of syllable card media in improving the reading readiness of elementary school students. The research employed a descriptive qualitative approach with a case study method. The study involved 14 first-grade students as research subjects. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The syllable card media consisted of cards containing syllables that could be combined to form new words, encouraging active student participation in reading activities. The results indicate that the use of syllable card media significantly improves students’ reading readiness, particularly in recognizing syllables, forming words, and increasing reading motivation. The implications suggest that syllable card media can serve as an effective alternative learning medium to foster reading readiness among early-grade elementary students.